Promoting Critical Thinking Skills Using Voice-Based Chatbots in an Integrated Listening and Speaking Class - Saulahirwan, Lely Desilia Flora; Widhiatama, Daniel Ari (Continuous Education: Journal of Science and Research, 2025)
This study aims to test the effectiveness of using voice-based chatbots (VBC) in improving students' critical thinking skills in integrated listening and speaking and to investigate their perspectives on the use of VBC in the classroom. This study uses a pre-experimental design to determine the effectiveness of using voice-based chatbots (VBC) in improving students' critical thinking skills in integrated listening and speaking classes and employs qualitative research methods such as interviews to explore students' perceptions of using voice-based chatbots to support their critical thinking and communication skills. The study involved 32 participants from a private university in Yogyakarta. The research results showed that the average pre-test score was 69.28 with a standard deviation of 3.78, and the average post-test score increased to 77.00 with a standard deviation of 4.83. In terms of descriptive statistics, there was an improvement in learning outcomes after using the chatbot. The paired-sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test scores after the intervention using the voice-based chatbot.